Pemanfaatan Media Sosial Dalam Pemasaran UMKM - Mutiara Sani Siagian; Nungraeni Nungraeni (Jurnal Pengabdian Masyarakat Nusantara, 2023)
This service activity explains how social media can be used to market MSME products in the Gamplong area. The purpose of the service is to introduce MSME products to the wider community in order to capture great potential. This research metdhod is descriptive qualitative. From the results of the service, it was found that the use of social media has good benefits in increasing sales of MSME products in the Gamplong area.